2019
DOI: 10.3357/amhp.5248.2019
|View full text |Cite
|
Sign up to set email alerts
|

Individual Attributes, Values, and Goals of an All-Military Women Antarctic Expedition

Abstract: BACKGROUND: While participation of women in the military has increased, research on performance of female teams engaged in arduous physical activity in isolated, confined, and extreme (ICE) environments remains sparse. METHODS: A team of six British military women completed the Multidimensional Personality Questionnaire-Brief Form, Triarchic Psychopathy Measure, and Personal Values Questionnaire (PVQ) prior to embarking on an expedition that traversed the Antarctic continent. Questionnaires were completed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…In common with results from similar Polar expedition studies, we found positive affect generally higher than negative affect across the entire expedition period (Blackadder-Weinstein et al, 2019; Kjaergaard et al, 2015; Leon, Sandal, Fink, et al, 2011). Daily reports of physical and psychological health were correlated (e.g., higher fitness scores were associated with lower reports of negative affect), highlighting the interdependency of the physical and psychological experience.…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…In common with results from similar Polar expedition studies, we found positive affect generally higher than negative affect across the entire expedition period (Blackadder-Weinstein et al, 2019; Kjaergaard et al, 2015; Leon, Sandal, Fink, et al, 2011). Daily reports of physical and psychological health were correlated (e.g., higher fitness scores were associated with lower reports of negative affect), highlighting the interdependency of the physical and psychological experience.…”
Section: Discussionsupporting
confidence: 88%
“…Although researchers have previously examined the physical and psychological function of Polar travelers (e.g., Anton-Solanas, O’Neill, Morris, & Dunbar, 2016; Blackadder-Weinstein, Leon, Norris, Venables, & Smith, 2019; Gifford et al, 2018; Leon, Sandal, Fink, & Ciofani, 2011), few studies have explored the situational or day-to-day dynamics that may explain variability in their experience. Studies conducted to date have rarely explored the interrelations between the events encountered, the reaction to those events, and the consequent impact upon physical and psychological health (for exceptions, see Kahn & Leon, 1994; Leon, Kanfer, Hoffman, & Dupre, 1991).…”
mentioning
confidence: 99%
See 3 more Smart Citations